2018
DOI: 10.18203/2349-3291.ijcp20184282
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of breastfeeding position and attachment (ABPA) in a tertiary care centre in Chennai, India: an observational descriptive cross-sectional study

Abstract: Background: Effective breastfeeding becomes an art with experience. Correct position and attachment is the first step necessary for exclusive breast feeding. However, studies assessing correct position and attachment for breastfeeding in South India are sparse. Hence our study aimed to assess the percentage of mother infant dyads with correct breastfeeding position and attachment along with factors influencing them in a Tertiary care Hospital.Methods: A descriptive cross-sectional study was conducted among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…A structured observational checklist adopted from the WHO breastfeeding observational checklist and interviewer-administered questionnaires was developed on reviewing different related literature 8 9 22 23 32. According to the WHO criteria, we developed and adopted an arbitrary scoring and grading system to grade positioning, infant’s mouth attachment and effective suckling during breast feeding 33.…”
Section: Methodsmentioning
confidence: 99%
“…A structured observational checklist adopted from the WHO breastfeeding observational checklist and interviewer-administered questionnaires was developed on reviewing different related literature 8 9 22 23 32. According to the WHO criteria, we developed and adopted an arbitrary scoring and grading system to grade positioning, infant’s mouth attachment and effective suckling during breast feeding 33.…”
Section: Methodsmentioning
confidence: 99%
“…This study finding was consistent with findings revealed in the different regions of Ethiopia, Libya, and India. 6 , 15 , 20 , 23 , 42 Improper breastfeeding techniques may cases uncomfortable and painful for the mother resulting in damage to the skin of the nipple, cracking, sore nipples, fissures, engorged, and blocked ducts, or mastitis. 8 , 35 , 43 This could be the reason for the difficulties in maintaining proper position, attachment, and suckling, resulting in ineffective breastfeeding techniques practiced.…”
Section: Discussionmentioning
confidence: 99%